Histopathological characteristics of surgical tissue from primary vs recurrent chronic rhinosinusitis with nasal polyposis patients - Donnell, Nathaniel J. (Laryngoscope Investig Otolaryngol, 2020)
OBJECTIVE: The histopathological characteristics of primary vs recurrent nasal polyps in patients with chronic rhinosinusitis with nasal polyps (CRSwNP) have not been studied comprehensively. Identification of these features may be helpful for prognostication, postoperative management, and consideration of novel eosinophil‐targeting biologic therapy. This study investigates the histopathological differences in primary vs recurrent CRSwNP tissue. METHODS: Patients undergoing endoscopic sinus surgery for CRSwNP were included if all 13 histopathological and mucin characteristics on a standardized report were available. Histopathology parameters were compared in surgical tissue and mucin from primary vs recurrent CRSwNP. RESULTS: Complete structured histopathology reports were available for 96 patients (39 primary polyps and 57 recurrent polyps). Compared to primary polyp tissue, recurrent CRSwNP mucin was significantly more likely to feature eosinophil aggregates (57.9% vs 35.9%; P = .047). Tissue eosinophilia (using a threshold >10 per high power field [HPF]) was not significantly different in primary and recurrent CRSwNP tissue. Other histopathologic parameters and clinical characteristics were similar. CONCLUSION: Eosinophil aggregates on histopathology are significantly more likely to be present in recurrent CRSwNP. In the limited series, tissue eosinophilia (>10 per HPF) was not significantly different in primary and recurrent CRSwNP. Therefore, in addition to the study of tissue eosinophilia levels, Rhinologic surgeons should also direct attention to CRSwNP mucin. Mucin eosinophilic aggregates are an independent marker of severe inflammation that is associated more likely with recurrent vs primary polyposis. Further study of this marker may help determine its role of choice of postoperative medical therapies, including anti‐eosinophilic biologics. LEVEL OF EVIDENCE: 4